Some comments on the nonlinear dynamics of a portal frame under base excitation - Paula, Aline Souza de; Balthazar, Jose Manoel [UNESP]; Palacios Felix, Jorge Luis (IOS Press, 2013)
This paper presents a nonlinear dynamic analysis of a flexible portal frame subjected to support excitation, which is provided by an electro-dynamical shaker. The main goal of this study is to investigate the dynamic interactions between a flexible portal frame and a nonlinear electrical support excitation. The numerical analysis shows a complex behavior of the system, which can be observed by phase spaces, Poincare sections and bifurcation diagrams.
Keywords: Electro-dynamical shaker; flexible portal frame; nonlinear dynamics